THE PROBLEM OF A LACK OF MATERIAL BEHAVIOUR DATA FOR RISK ASSESSMENT - Bondarenko, I. O.; Neduzha, L. O. (Science and Transport Progress, 2021)
Purpose. The main purpose of this work is to provide theoretical support for the need to expand data on changes in the material behaviour under dynamic loads when railway track risk assessment over time due to railway track elements deformability. Methodology. For the research, an original model of railway track design described using the original method based on the ability of elastic waves to propagate energy of power pulses in space and time, as well as a model describing materials as discrete substances were used. Findings. It has been established that the properties of the material affect the deformability of the elements and the design of the railway track; the main parameter in the study of deformability processes is time; material, as a substance, consists of atoms and molecules, and therefore is not continuous; internal physical processes determine changes in the behaviour of the material of an element. Originality. It has been proposed to develop classifications of changes in the physical properties of materials according to the probability of irreversible deformations and the impossibility of deformations, as well as classifications of changes in the mechanical properties of materials according to the probability of the defect appearance and changing the material structure. Practical value. The ability to simulate analytically any physical processes occurring inside elements due to the proposed method allows combining the influence of mechanical and physical effects into a single calculation. This enables to assess the probability of appearing defects in elements under certain dynamic loads when assessing the railway track risk over time due to railway track elements deformability.